2015
DOI: 10.1007/s11595-015-1195-5
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and plastic behaviors of laminated Ti-TiBw/Ti composites

Abstract: The novel laminated Ti-TiBw/Ti composites composed of pure Ti layers and TiBw/Ti composite layers have been successfully fabricated by reactive hot pressing. Herein, two-scale structures formed: the pure Ti layer and TiBw/Ti composite layer together constructed a laminated structure at a macro scale. Furthermore, TiBw reinforcement was distributed around Ti particles and then formed a network microstructure in TiBw/Ti composite layer at a micro scale. The laminated Ti-TiBw/Ti composites reveal a superior combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, shear fracture failure is always located at the decarburized layer as shown in Figure 8b. Liu et al [104][105][106] used the hot pressing to join and pin the interface by reacted TiB whisker between Ti and TiB 2 , and the interface bonding strength is higher than that of the soft layer. The interface alloy elements' diffusion is decreased, while the fracture elongation is increased by adding the Ni interlayer.…”
Section: Interface Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, shear fracture failure is always located at the decarburized layer as shown in Figure 8b. Liu et al [104][105][106] used the hot pressing to join and pin the interface by reacted TiB whisker between Ti and TiB 2 , and the interface bonding strength is higher than that of the soft layer. The interface alloy elements' diffusion is decreased, while the fracture elongation is increased by adding the Ni interlayer.…”
Section: Interface Structurementioning
confidence: 99%
“…The interface microstructure and fracture characteristics of different laminated metal composites. (a,b) stainless steel clad plate, adapted from[100][101][102][103], with permission from publisher: Elsevier, 2019; (c,d) laminated Ti-TiBw/Ti composites, adapted from[104][105][106]111], with permission from publisher: Elsevier, 2019; (e,f) laminated Ti-Ti 3 Al composites, adapted from[112], with permission from publisher: Elsevier, 2019.…”
mentioning
confidence: 99%
“…Huang et al [2,23,24] concluded that the titanium matrix composites with network structure correspond to the upper limit of Hashin-Shtrikman (H-S) bound. Based on H-S bounds proposed by Hashin and Shtrikman in 1963 [25,26], the reinforcement with network structure can be viewed as "stiffer" phase, which is continuous and encapsulates the titanium matrix as shell structure.…”
Section: Multiscale Hierarchical Structurementioning
confidence: 99%